ChemInform Abstract: Ruthenium(II)‐Catalyzed Synthesis of Pyrrole‐ and Indole‐Fused Isocoumarins by C—H Bond Activation in DMF and Water. Issue 31 (14th July 2016) - Singh, Keisham S.; Sawant, Sneha G.; Dixneuf, Pierre H.
Abstract: The title reaction uses pyrrole‐2‐carboxylic acids and indole‐3‐carboxylic acids as starting material and copper acetate as oxidant.